Le tipologie di albero nelle drupacee - Bassi, Daniele (Milano University Press, 2022)
This monograph focuses important points related to growth habits in stone fruit trees and represents a significant contribution to the field of breeding for improved fruit tree growth habit. A team of experts in the field have produced an information platform based on an orderly and coordinated set of measured parameters. Each growth habit within a species is defined and discussed, terms are defined (glossary), objective tree growth data are presented, and reference cultivars are provided. Illustrations represent a useful visual guide to each growth type. This monograph thus seeks not only to describe the main tree habits found in five important stone-fruit species but also to identify the morphological keys unlocking their characterization and, in the process, provide some suggestions for their practical exploitation.